Dynamic Micro-Macro Market Coordination and Technical Change - Gunnar Eliasson (The Research Institute of Industrial Economics (IUI), 1985)
This paper discusses the nature of macro productivity change from the perspective of a Schumpeterian micro-to-macro (M-M) model. It emphasizes the dynamics of resource allocation through markets (firms) where agents are both price and quantity setters. We find that the organization of market processes (the market regime) is important for the rate of total factor productivity change at aggregate levels . This is especially so when relative prices are shifty as a consequence of the ongoing market process and markets, notably the capital markets, are in disequilibrium.
Keywords: E61; H11; O40; 330; Role of goverment; macro productivity; micro-to-macro model; technological change; Ökonometrisches Makromodell; Marktmechanismus; Technischer Fortschritt; Produktivität